Market Efficiency of Rubber: An Analytical Study Based on Co-integration Technique - Kumar, M. P. Sharath; Suresh, P. R. (International Journal of Bio-resource and Stress Management, 2017)
India is the fourth largest producer of Natural Rubber which accounts 7% of world production. It is found that more than 12 lakh farmers directly depend on Natural Rubber for their livelihood strategies. When we analyses the global Natural Rubber market, we can see that in the recent years there is a sharp decline in the market prices of Natural Rubber at internationally and domestically. The present study analyses the interdependence of domestic and international market prices with the use of Co-integration technique to prove market efficiency. The integration of rubber market is measured by using the time series data from 2012–2015. By taking the data on rubber prices in the Kottayam market in India as domestic price, and Bangkok rubber market as the international price. Error Correction Model (ECM) for long run relationship and Granger Causality tests were also used for an in-depth analysis. The Granger test result indicates that there is causality in at least one direction, i.e. Bangkok price causes the price in Indian market as the p-value is 0.0399 which is less than level of significance at 5%. Overall, there is sufficient evidence to conclude that Indian rubber market is integrated with the Bangkok market in the long-run. The recent fall in domestic price of Natural Rubber was due to a fall in the international price.